Perjumpaan Dengan Allah: Iman, Harapan, dan Kasih Menurut Santo Yohanes Dari Salib - Alnija, Marianus Dinata; Lektawan, Fedrianus Korintius (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
This research investigates the perspective of Saint John of the Cross regarding encounters with God through the lenses of Faith, Hope, and Love, as elucidated in the renowned work titled